IMPLEMENTASI MEDIASI PENAL TERHADAP TINDAK PIDANA PENIPUAN DI KEPOLISIAN RESOR KAMPAR - Dian Oktami; Mexsasai Indra; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
In everyday life humans are often faced with an urgent need, to fulfill it, often carried out without careful thought such things will have a negative effect that is not balanced with a life of good value. To restore a good life, a responsibility of the perpetrators is needed in the form of a delegation of a sense of community discomfort that can be felt as well as the suffering or loss experienced. Delegation is carried out by an individual or group of people authorized for it as an assignment given by the community to him. Meanwhile, for the recipient of an abundance in taking responsibility for his actions, it is in the form of punishment which is called criminal and lately there are often changes in Indonesian society that are then known with a moral crisis that is one form of crime that is still very common in society, namely fraud, in positive Indonesian law the principle of criminal cases cannot be resolved outside the court, although in certain cases it is possible to settle cases outside the court. However, law enforcement practices in Indonesia are often also criminal cases resolved outside the court through the discretion of law enforcement officials, peace mechanisms, adat institutions and so on.This research is a type of sociological legal research, which is research that wants to see the unity between law and society with the gap between das solen and das sein. The study was conducted at the Kampar Resort Police because the authors describe how the Implemantation of Penal Mediation Against Fraud Crimes in the Kampar Resort Police, this location was chosen because many Fraudulent Crime cases were Penal Mediation but were not suitable for mediation, and did not filter out the appropriate cases for Mediation and which is inappropriate for Mediation.The results of the research conducted by the author are, it is expected that the implementation of the application of mediation of the penal that is in accordance with the punishment of the perpetrators of fraud in Kampar resort police in relation to the integrated criminal justice system and also this restorative justice so that the perpetrators of the criminal acts of fraud have a sense of effect to him so that in the future the perpetrators will not commit fraud again.Keywords: Crime, Fraud, Penal Mediation